Pengaruh Carbon Emission Disclosure Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kinerja Lingkungan Sebagai Variabel Moderasi - Tanti Hardianti; Susi Dwi Mulyani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to empirically determine the effect of Carbon Emission Disclosure (CED) and firm size on firm value with environmental performance as a moderating variable. This study uses a quantitative approach using secondary data. The sample was selected using a purposive sampling technique with a population of non-financial companies registered on the IDX from 2019 - 2021. This study uses multiple linear regression techniques to test the hypothesis using the SPSS program. The results of the study show that carbon emission disclosure has a positive effect on the firm's value. The results of this study also reveal that environmental performance has a significant positive effect on firm value, so it can be concluded that PROPER can be used as a company signal to increase firm value.